Effects of two dietary crude protein levels on finishing performance, meat quality, and gene expression of market lambs. (7th October 2021) - Wang, Yongjie; Shelby, Sarah; Apple, Jason; Coffey, Ken; Pohlman, Fred; Huang, Yan
Abstract: Seventeen crossbred lambs were assigned randomly to low‐protein (LP; 8% crude protein [CP]; n  = 9) and high‐protein (HP; 13% CP; n  = 8) diets for 9 weeks. The final body weight, average daily feed intake (ADFI), and average daily gain (ADG) of the HP lambs were significantly higher ( P  < 0.05) than the LP lambs; however, gain to feed ratio (G:F) for the LP lambs was significantly higher ( P  < 0.05) than the HP lambs. Hot carcass weight (HCW), adjusted fat thickness, and drip loss of longissimus dorsi ( LD ) muscle were significantly higher ( P  < 0.05) for the HP than LP lambs. In contrast, instrumental color values L *, a*, b *, C *, and hue angle ( H ) of meat from the LP lambs scored significantly higher ( P  < 0.05) than the HP lambs. The LD muscle from HP lambs had significantly greater CLA of cis ‐9 trans‐11 isomer ( P  < 0.05) than the LP lambs. The gene expression of metabolism and meat quality‐related genes of LP was significantly higher than HP ( P  < 0.05). These results suggest that a higher dietary CP level promotes growth performance for finishing lambs, whereas lower dietary CP level is beneficial for meat quality, especially when evaluating color characteristics in the final product.